A construção social de envelhecer e envelhecimento: atravessamentos contemporâneos - Oliveira, Joice Preuss (My University, 2025)
This Final Course Work (TCC) in Social Work discusses aging and the process of growing old in the contemporary context. The research problem guiding this study is: How is contemporary aging socially constructed, and how do these particularities produce different ways of growing old in Brazil? The objective is to understand and analyze aging as a social construct and the specific conditions that shape different ways of growing old in the country. To this end, Critical Social Theory was employed through the Historical-Dialectical Materialist Method, with emphasis on the categories of historicity, totality, mediation, and contradiction. Documental and bibliographic research were used as methodological procedures. In the results and discussion, the initial aim was to comprehend aging and the process of growing old as a social construct, highlighting that this trajectory is marked by historical, political, cultural, and social determinations that shape distinct experiences of old age. Based on the analysis of classical and contemporary authors, it was identified that aging in Brazil is traversed by inequalities accumulated throughout the life course, especially among generations who experienced youth and adulthood in contexts lacking social protection. With the advancement of legal frameworks and social public policies directed at older adults, such as the Elderly Statute (2003) and the National Health Policy for Older Persons (2006), aging began to be recognized as a public issue. However, setbacks and limitations become evident, which particularize and characterize the current scenario: the dismantling of social policies, the commodification of care, and an exclusionary digital era, all of which shift responsibilities from the State to families and the market. Thus, challenges in the contemporary context are signaled: the retrenchment of social protection and the targeting of policies; the commodification of care and the transfer of responsibilities to families; digital exclusion and the bureaucratization of access to rights; and the intersectional inequalities and stigmas that permeate aging. [resumo fornecido pelo autor]
O presente Trabalho de Conclusão de Curso (TCC) em Serviço Social disserta sobre o envelhecer e o envelhecimento no cenário contemporâneo. A questão colocada como problemática de pesquisa é: De que forma o envelhecimento contemporâneo é construído socialmente e como essas particularidades produzem diferentes modos de envelhecer no contexto brasileiro? E objetiva compreender e analisar o envelhecimento enquanto construção social e as particularidades que produzem diferentes modos de envelhecer no Brasil. Para tanto, utilizou-se a Teoria Social Crítica por meio do Método Materialista Histórico Dialético, com destaque para as categorias de historicidade, totalidade, mediação e contradição. Utilizou-se, como procedimentos metodológicos, a pesquisa documental e bibliográfica. Nos resultados e discussões, inicialmente, buscou-se compreender o envelhecimento e o envelhecer como construção social, evidenciando que essa trajetória é marcada por determinações históricas, políticas, culturais e sociais que configuram formas distintas de viver a velhice. A partir da análise de autores clássicos e contemporâneos, identificou-se que o envelhecimento no Brasil é atravessado por desigualdades acumuladas ao longo da vida, expressas especialmente nas gerações que vivenciaram juventude e vida adulta em contextos de ausência de proteção social. Com o avanço de marcos legais e políticas públicas sociais voltadas à pessoa idosa, como o Estatuto da Pessoa Idosa (2003) e a Política Nacional de Saúde da Pessoa Idosa (2006), o envelhecimento passa a ser reconhecido como questão pública. Entretanto, evidenciam-se retrocessos e limites que particularizam e caracterizam o cenário atual: O desmonte das políticas sociais, a mercantilização do cuidado e a era digital excludente, que deslocam responsabilidades do Estado para as famílias e para o mercado. Sinalizam-se, assim, desafios no contexto contemporâneo: retração da proteção social e a focalização das políticas; a mercantilização do cuidado e a transferência de responsabilidades às famílias; a exclusão digital e a burocratização do acesso a direitos; as desigualdades interseccionais e os estigmas que atravessam o envelhecimento. [resumo fornecido pelo autor]
Keywords: Serviço social; Envelhecimento - Aspectos sociais; O Contemporâneo